Compaction of smectite-rich mudstone and its influence on pore pressure in the deepwater Joetsu Basin, Sea of Japan. (December 2016) - Nguyen, Binh Thi Thanh; Kido, Machiko; Okawa, Naoki; Fu, Han; Kakizaki, Satoshi; Imahori, Seiichi
Abstract: Pore pressure prediction is needed for drilling deepwater wildcats in the Sea of Japan because it is known from past experience that there can be drilling problems can arise due to overpressure at shallow depths. The "Joetsu Basin" area is located offshore to the southwest of Sado Island on the eastern margin of the Sea of Japan. The sedimentary succession of the Neogene is mainly composed of turbidite sediments which contained smectite-rich mudstones. The cause of overpressure in the study area is expected to be a combination of mechanical disequilibrium compaction and chemical compaction, especially from the illitization of smectite. We have constructed basin models and performed numerical simulations by using 1D and 3D PetroMod to understand clearly the history of fluid flow and overpressure development in the lower Pliocene Shiya Formation and Middle to Upper Miocene Teradomari Formations. A compaction model coupled with both mechanical and chemical compaction for smectite-rich sediments is used for pore pressure calibration. We have examined three key relationships: porosity-effective stress, porosity-permeability, and the kinetics of smectite-illite transformation. We determined the ranges for the parameter values in those relationships that allow a good fit between measured and modelled pore pressures to be obtained. Results showed that for the most likely case, high pore pressure in the Lower and Upper Teradomari developed since 8.5 Ma and 5.5 Ma, respectively. Pore pressures in studied structures have approximately doubled since 1 Ma due to the high deposition rate of the Pleistocene Haizume Formation and smectite-illite transformation in the lower Pliocene-Shiya and Middle to Upper Miocene- Lower and Upperr Teradomari formations. In three cases (high case, most likely case and low case), the overpressures in the Shiya, Upper and Lower Teradomari Formations are less than 1 MPa, 15 and 30 Ma, respectively. The results provide a basis for planning future wells in the "Joetsu Basin" area and in other basins where geological conditions are similar, i.e., deepwater, high sedimentation rate, high geothermal gradient and smectite-rich sediments. Highlights: Overpressure in the study area has been generated by disequilibrium compaction and transformation of smectite to illite. A compaction model coupled with both mechanical and chemical compaction for smectite-rich sediments is used for pore pressure calibration. We determined the ranges for the parameter values in three key relationships that allow a good fit between measured and modelled pore pressures. High pore pressure developed since 8.5 Ma and 5.5 Ma, respectively. In studied structures present pore pressures are about twice as high as they were at 1 Ma.